Bycatch from seagrass fisheries: implication for conservation. Issue 1 (October 2021) - Ambo-Rappe, R; La Nafie, Y A; Marimba, A A; Rismayani, A; Unsworth, R K F
Abstract: Fishing activities conducted on seagrass bed to capture fishes and other seagrass associated fauna are very massive especially in the Pacific regions and undeveloped countries. This is due to the high abundance of economically important species associated to seagrasses, and additionally, seagrass area is the most accessible fishing ground throughout the year and with low capital. Seagrass meadows are importance habitat to support an abundance and diverse fish assemblages that form the basis for artisanal fisheries, which are vital in maintaining food security of coastal community in the regions. The seagrass fishery is considered a small-scale, multi-species and multi-gear fisheries. One of the fishing gear used in this fishery is traditional permanent fish trap called " sero ". Bycatch from some small-scale fisheries have been reported such as from trawls, traps, gill nets, and longline fisheries. This study aimed to identify bycatch species from " sero ", a type of seagrass fisheries which is in the form of fish fences with nets positioned on intertidal area of seagrass bed to the subtidal for approximately 200m. The result shown the bycatch from this fisheries was dominated by either low value fishes or invaluable and even toxic fishes for consumption, such as the puffers (Tetraodontidae and Diodontidae), juveniles of Apogonidae and Chaetodontidae. Additionally, sharks, turtles, and rays were also found in the bycatch. This result should be put into consideration as the bycatch would have an ecological consequences on the population, predator-prey relationship, and ecosystem resilience to stressor in general. Information from this study will be important for sustainable small-scale fisheries management and seagrass conservation, and therefore, further research into bycatch reduction in this fishery would be desirable.